Tinjauan Yuridis Terhadap Kewenangan MPR Dalam Melakukan Perubahan Undang-Undang Dasar - Munif Rochmawanto (Universitas Islam Lamongan, 2013)
In a lawful country, the existence of constituent is one of the most important requirements to control a country. Hence, it is also required for Indonesia; which had put its society life rules fully in a constituent (UUD 1945). By far, Indonesia has faith that the importance of a constituent‟s existence will take effect for a greater life in nation society‟s needs. The change in a constituent or UUD in a country, for instance, will be done by a competent national bureau. In Indonesia, such competency is obtained by Majelis Permusyawaratan Rakyat (MPR). Meanwhile, the reformation era takes its role in year 1998, and then MPR held the court to discuss about the change in UUD 1945 for some times ahead; at 19th of October 1999, the first change had done, at 18th of August 2000, the second change had done, and also, at 10th of November, the third change had done, and finally at 10th of August 2002, the fourth change had done too.Keywords : Juridic observation, MPR Rights, The Change in UUD